Metagenomics as a Diagnostic Method for Identifying Microbiota Profiles in Diarrhea Cases - Rahmat Apipi; Linda Erlina (Eduvest - Journal of Universal Studies, 2026)
Diarrhea remains a major global health issue and is one of the leading causes of morbidity and mortality, especially in children. Changes in the composition of gut microbiota are strongly associated with the occurrence of diarrhea, particularly due to infections caused by pathogenic microorganisms. Conventional diagnostic techniques, such as culture, still have limitations in detecting diverse and unculturable microbes. Metagenomics offers a comprehensive diagnostic solution by analyzing the entire genetic material directly from stool samples using sequencing-based approaches. This review discusses two metagenomic strategies—16S rRNA sequencing and whole-genome shotgun metagenomic sequencing—based on studies conducted in India and Peru. The 16S rRNA approach enables the identification of bacterial community structure and dysbiosis in diarrhea cases, while shotgun metagenomics provides higher resolution for detecting pathogenic species, including Campylobacter spp., and co-infections that are often missed by standard methods. Both techniques demonstrate significant advantages in detecting microbiota diversity, identifying novel pathogens, and uncovering antimicrobial resistance profiles. Therefore, metagenomics represents a promising diagnostic tool for improving the accuracy of diarrhea detection and supporting public health interventions in endemic regions.